Answer:
3CCl4 + 2SbF3 → 3CCl2F2 + 2SbCl3
Step-by-step explanation:
CCl4 +SbF3 → CCl2F2 + SbCl3
On the left side we have 3 times F, on the right side we have 2 times F
To balance we have to multiply SbF3 (on the left side) by 2
On the right side, we have to multiply CCl2F2 by 3
CCl4 +2SbF3 → 3CCl2F2 + SbCl3
On the left side we have 2x Sb, on the right side we have 1x Sb
So we have to multiply, on the right side, SbCl3 by 2
CCl4 +2SbF3 → 3CCl2F2 + 2SbCl3
On the right side, we have 12 times Cl, on the left side we have 4 times Cl
We have to multiply, on the left side, CCl4 by 3. The balanced equation is:
3CCl4 + 2SbF3 → 3CCl2F2 + 2SbCl3